SIGNIFICANCE OF BUSINESS QUALITY MANAGEMENT FOR INCREASING COMPETITIVENESS OF SERBIAN ECONOMY - Marija Andjelković Pešić; Vesna Janković Milić; Jelena Stanković (Serbian Journal of Management, 2012)
This paper points out some challenges Serbian economy is facing at the beginning of the XXIcentury. Based on the fact that the quality, both in theory and practice, has been promoted as the mostimportant dimension of competitiveness, improvement of quality stands out as the primary task ofenterprises in Serbia. In the last part of the paper there are some results of the research, conductedwith purpose of identifying opportunities for improving the quality of business in Serbian economy.The authors have been trying to establish the connection between Serbia’s competitiveness ratingaccording to research results of confidential institutions (World Bank’s Report on Business, GlobalCompetitiveness Report 2010-2011) and presence of quality management concepts and tools inbusiness practice in Serbia. The intention of the authors is to present the research results and toindicate the possibilities for improving competitiveness of Serbian economy, primarily throughimplementation of modern management concepts and models. The one that is suggested in this paperis the Six Sigma concept.